2018
DOI: 10.3389/fonc.2018.00521
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy and Epigenetic Pathway Modulation in Glioblastoma Multiforme

Abstract: Glioblastoma Multiforme (GBM) is the most common malignant primary brain tumor. Despite aggressive multimodality treatment it remains one of the most challenging and intractable cancers (1]. While current standard of care treatment for GBM is maximal safe surgical resection, systemic chemotherapy with Temozolimide (TMZ), and radiation therapy, the current prognosis of GBM patients remains poor, with a median overall survival of 12–15 months (2, 3). Therefore, other treatments are needed to provide better outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Several promising novel immunotherapeutic approaches are being actively investigated in clinical trials for GBM treatment ( Figure 1 ) [ 7 , 8 , 9 , 10 , 11 ]. These include inhibitors of immune checkpoint regulators, antitumor vaccinations, adoptive transfer of genetically modified and cytotoxic T-lymphocytes, and generation of genetically engineered oncolytic viruses.…”
Section: Immunotherapeutic Approaches For Glioblastomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Several promising novel immunotherapeutic approaches are being actively investigated in clinical trials for GBM treatment ( Figure 1 ) [ 7 , 8 , 9 , 10 , 11 ]. These include inhibitors of immune checkpoint regulators, antitumor vaccinations, adoptive transfer of genetically modified and cytotoxic T-lymphocytes, and generation of genetically engineered oncolytic viruses.…”
Section: Immunotherapeutic Approaches For Glioblastomasmentioning
confidence: 99%
“…In the quest for an effective treatment, several immunotherapeutic approaches have been introduced in recent years that have been designed to harness patient’s immune response to fight and eliminate tumor cells. Broadly, these novel strategies can be divided into four major classes: immunomodulators, active immunotherapy, adoptive immunotherapy, and oncolytic viral therapy [ 5 , 6 , 7 , 8 , 9 , 10 , 11 ]. Although immunotherapy has yet to be established for providing consistent clinical benefits in GBM, several immunotherapy trials have reported acceptable safety profiles and survival benefits in small cohorts of patients [ 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since Th1 is one of main anti-tumor functioning T lymphocytes and the induction of Tregs is one of the mechanisms for immunosuppression and immune evasion of tumor cells [ [183] , [184] , [185] ], these siRNA-loaded PEG-chitosan-lactate nanomedicines could effectively stimulate anti-tumor immune responses selectively at the tumor sites without systemic injection of A2AR antagonists that may cause unwanted side effects through induction of Th1 and suppression of Tregs. As the induction of antitumor immune responses requires activation or inhibition of different receptors or signaling pathways, administration of multi-type nucleic acids targeting at different pathways may have the potential to further enhance the efficacy of cancer immunotherapy [ 186 , 187 ]. However, how to achieve co-delivery of different nucleic acids to targeting sites and simultaneously maintain their inherent bioactivity, is still a great challenge.…”
Section: Chitosan-based Nanomedicinesmentioning
confidence: 99%
“…Immunotherapy alone and in combination with radiation and chemotherapy is currently explored as a method for glioblastoma treatment [119], but it still needs to prove its clinical importance. The importance of lncRNAs in immune regulation of glioblastomas is also being examined.…”
Section: Immune-related Long Noncoding Rnasmentioning
confidence: 99%